2018
DOI: 10.3389/fmicb.2018.01007
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Pseudomonads Inhibit Oomycete Plant Pathogens of Glycine max

Abstract: Seedling root rot of soybeans caused by the host-specific pathogen Phytophthora sojae, and a large number of Pythium species, is an economically important disease across the Midwest United States that negatively impacts soybean yields. Research on biocontrol strategies for crop pathogens has focused on compounds produced by microbes from soil, however, recent studies suggest that aquatic bacteria express distinct compounds that efficiently inhibit a wide range of pathogens. Based on these observations, we hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 61 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…Given the molecular structure of this tryptophan derivative, one might indeed speculate that it is an intermediate in the kynurenine pathway, which has been implicated in the biosynthesis of (non-volatile) antimicrobial and cell-cell communication signals such as quinolones (Gross and Loper, 2009) or the siderophore thioquinolobactin involved in anti-oomycete activity (Matthijs et al, 2007). Moreover, a recent study identified a genomic locus in a Pseudomonas strain involved in anti-oomycete activity, which contained several genes encoding different steps of the kynurenine pathway (Wagner et al, 2018). Although the biosynthesis and biological activity of L -dihydroxanthurenic acid is so far unknown, this newly detected volatile might be an interesting candidate for further studies of its potential implication in the inhibition of oomycetes such as P. infestans or P. viticola.…”
Section: Discussionmentioning
confidence: 99%
“…Given the molecular structure of this tryptophan derivative, one might indeed speculate that it is an intermediate in the kynurenine pathway, which has been implicated in the biosynthesis of (non-volatile) antimicrobial and cell-cell communication signals such as quinolones (Gross and Loper, 2009) or the siderophore thioquinolobactin involved in anti-oomycete activity (Matthijs et al, 2007). Moreover, a recent study identified a genomic locus in a Pseudomonas strain involved in anti-oomycete activity, which contained several genes encoding different steps of the kynurenine pathway (Wagner et al, 2018). Although the biosynthesis and biological activity of L -dihydroxanthurenic acid is so far unknown, this newly detected volatile might be an interesting candidate for further studies of its potential implication in the inhibition of oomycetes such as P. infestans or P. viticola.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports on plant-associated pseudomonads indicated also a role of siderophores, lytic enzymes, hydrogen cyanide and ammonia as well as organic volatiles in the inhibition of fungal phytopathogens ( Alimi et al, 2012 ; Loper et al, 2012 ; MĂĽller et al, 2013 ; Zhang et al, 2014 ; De Vrieze et al, 2015 ; Yasmin et al, 2016 ). Wagner et al (2018) most recently examined Pseudomonas strains to identify the gene clusters that are responsible for antagonism against oomycetes by transposon mutagenesis combined with high throughput sequencing and antagonism tests. As a result of these in-depth investigations, the expression of a specific siderophore was determined.…”
Section: Discussionmentioning
confidence: 99%
“…A natural product from the marine bacterium Pseudoalteromonas was able to inhibit a multidrug efflux pump, thus increasing the effects of antibiotics against MDR pathogens (10). Last, lake-derived pseudomonads were active at inhibiting Pseudomonas aeruginosa (11), as well as oomycete plant pathogens (12). Although the prediction of BGCs from metagenomics data and the discovery of new compounds suggest a continued source for antibiotic discovery, the abundance of novel compounds effective against MDR pathogens remains unknown.…”
Section: Introductionmentioning
confidence: 99%